Efeitos da internacionalização no desvio da estrutura de capital alvo e na velocidade de ajuste - Carvalho, Larissa de Souza (2016)
This dissertation investigates the effects of internationalization in two gaps related to the capital structure that have not been discussed by the Brazilian literature yet. To this, were developed two independent sections. The first examined what the effects of internationalization on the deviation from the target capital structure. The second examined what the effects of internationalization on speed of adjustment (SOA) of the capital structure. It used data from Brazil, multinational and domestic companies, from 2006 to 2014. The results of the first analysis indicate that internationalization helps reduce the difference between the target and the current debt. That is, to the extent that the level of internationalization increases; whether only export or a combination of export, assets and employees abroad, the gap between the current structure and the target structure decreases. This reduction is given as a function of internationalization as a consequence of the upstream effect of the upstream-downstream hypothesis. Thus, as the Market Timing theory, it can be seen as an opportunity for adjustment of the capital structure, and with the reduction of deviation, there is also a reduction in the cost of capital of the firm. The result of the second analysis indicates that internationalization is able to significantly increase the speed adjustment, ensuring for the multinational a faster adjustment of its capital structure. Exports increase the SOA in 9 to 23%. And when also kept active assets and employees abroad the increase is 8 to 20%. In terms of time, while domestic company takes more than three years to reduce half of the deviation that has, while multinacional companies take on average one and a half year to reduce the same proportion of the deviation. The validity of the upstream-downstream hypothesis for the effect of internationalization in SOA was confirmed by comparing the results for US companies. Thus, the phenomenon of internationalization increases SOA when companies are from less stable markets, such as Brazil; and it has a less significcative effect when companies are derived from more stable markets, because they already have a high speed of adjustmennt. In addition, the adequacy analysis of the estimators also showed the model pooled OLS (Ordinary Least Squares) presents the highest quality in predicting the SOA than the system GMM (Generalized Method of Moments). For future studies it is suggested to analyze the effect of international event, by itself, and to validate the hypothesis using samples of different markets and the use of other estimators.